A Community-Based Differentiated Arabic Learning Model within Indonesia’s Merdeka Curriculum: Empirical Evidence from Islamic Primary Education - Nadhif, Moh.; Bakhiet, Bakri Muhammad (Fakultas Keguruan dan Ilmu Pendidikan,Universitas Jambi, 2026)
This study aims to analyze the effectiveness of the Community-Based and Differentiated Arabic Language Learning Model (CBDALM) within the framework of the Merdeka Curriculum in developing reading and writing skills among elementary school students, particularly in light of the limited implementation of differentiated instruction and project-based learning in this context. The study employed a mixed-method approach using a quasi-experimental design with pre-test and post-test control groups. The sample consisted of elementary students in an Islamic educational settingThe results revealed statistically significant differences in favor of the experimental group in both reading and writing skills, with a large effect size. In addition, there was a noticeable improvement in student engagement through interactive and contextual learning activities. The study contributes by proposing an integrative instructional model that combines differentiated instruction and project-based learning within an Islamic educational context.